Perkembangan Kaligrafi dan Urgensinya bagi Khazanah Mushaf - Abdul Hakim Syukrie (Jurnal Lektur Keagamaan, 2021)
Arabic script existed before the arrival of Islam, but it's just growing fast since the decline of the Al-Qur'an (Islam). It becomes an inseparable part of the Al-Qur'an and an important part of the mushaf history. Calligraphy has become the art of Islamic art not only because of its beauty, abstract, dynamic, modular structure, and combinative but because it makes Al-Qur'an as an object of creation. This article is a review of a book Khaṭ al-Muṣḥaf al-Syarīf wa Taṭawwuruhu fi al-'Ālam al-Islāmī by Abdul Aziz Hamid Saleh. He studied the development of Qur’anic calligraphy based on Islamic cultural areas: Hijāz, Syām, Iraq, Egypt, Spain, India, Far East, and South East Asia. The steps to reviewing this book are summarizing and analyzing. This book elaborates the science of calligraphy with history of Qur’anic manuscripts in the Islamic world. This paper emphasizes that calligraphy has characteristics that represent the place and the time it was developed. Based on the khat used, a Qur’anic manuscript can be revealed from which region and era it was copied. Therefore, calligraphy is an alternative method for studying the history of Qur’anic manuscripts apart from studying the colophon, types of paper, illumination and radiocarbon dating.  Keywords: Islamic calligraphy, Islamic art, Qur’anic manuscript.   Tulisan Arab sudah ada sebelum kedatangan Islam. Ia baru berkembang pesat setelah turunnya Al-Qur’an (Islam). Ia menjadi bagian tidak terpisahkan dari Al-Qur’an dan bagian penting dari sejarah mushaf. Kaligrafi menjadi seninya seni Islam bukan saja karena keindahannya, sifat abstrak, dinamis, struktur modular, dan kombinatif tetapi utamanya karena menjadikan Al-Qur’an sebagai objek kreasi. Artikel ini merupakan ulasan atas buku Khat al-Muṣḥaf al-Syarīf wa Taṭawwuruhu fi al-‘Ālam al-Islāmī karya Abdul Aziz Hamid Saleh. Ia mengulas sejarah perkembangan kaligrafi mushaf berbasis wilayah kebudayaan Islam: Hijaz, Syam, Iraq, Mesir, Andalus, India, dan Asia Jauh. Langkah yang dilakukan dalam mengkaji buku ini, yaitu mengikhtisarnya kemudian menelaahnya. Buku ini mengelaborasi ilmu kaligrafi dengan kajian sejarah mushaf al-Qur’an di dunia Islam. Tulisan ini menggaris bawahi sebuah mushaf Al-Qur’an dapat diungkap sejarahnya berdasar khat yang digunakan. Oleh sebab, itu Kaligrafi menjadi metode alternatif untuk menelaah sejarah mushaf Al-Qur’an selain melalui telaah kolofon, jenis kertas, ragam hias, dan uji karbon. Kata Kunci: Kaligrafi Islam, Mushaf Al-Qur’an, Seni Islam.